PROSEDUR AUDIT SUBSTANTIF ATAS SALDO KAS DAN SETARA KAS PT YZ OLEH KAP JAPP - Rizqi Adicandra (2023)
Audit is a process carried out by a competent and independent person in collecting and evaluating evidence of measurable information regarding the company's finances. Cash is the most liquid current asset, can be used at any time and almost every company transaction with other parties can affect cash. The purpose of this study was to determine the substantive procedures for cash and cash equivalents and the reporting of cash and cash equivalents audit results at KAP JAPP. The method used in this study is descriptive qualitative based on research results, substantive procedures on cash and cash equivalent accounts can be carried out by the auditor with the aim of gathering sufficient and sufficient evidence regarding the accuracy and completeness of the amounts, details and disclosures contained in the financial statements. KAP JAPP gave an opinion that the company's financial statements PT. YZ has been presented fairly in all material respects in accordance with the policies of financial accounting standards in Indonesia. So the Auditor does not make adjustments. Author's suggestion for PT. YZ is that in the future the branch's cash book should be updated more frequently.